2019
DOI: 10.1590/1806-9061-2018-0892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin E Supplementation on Serum Hormones and Gene Expression of Anti-Season Breeding Xingguo Grey Geese (Anser Cygnoides)

Abstract: The objective of this study was to analyse the impact of dietary vitamin E supplementation on laying performance, serum reproductive hormones concentration and gene expression in ovary and follicles of anti-season breeding goose. A total of 210 anti-season breeding geese were divided into seven treatments with six replications. Each group was supplied with diets containing different vitamin E (DL-α-tocopherol acetate) contents (0, 10, 20, 40, 80, 160, 320mg/kg). We observed that the egg production and laying r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Reham et al (2020) stated that diet supplemented with 0.3% Moringa oleifera seed powder upregulated the expression of mRNA of FSHR in laying quail, which is associated with higher egg production. Another study showed that breeding geese fed on diet supplemented with 80 mg/kg vitamin E gives the highest egg number which is associated with the increase in mRNA expression of FSHR and LHR genes (Yin et al 2019). The current study agrees with Elizabith et al (2000) who stated that FSH exert its role by its specific receptor (FSHR) in the development and maturation of the follicles and cooperates with LH in the ovulation process.…”
Section: Discussionsupporting
confidence: 91%
“…Reham et al (2020) stated that diet supplemented with 0.3% Moringa oleifera seed powder upregulated the expression of mRNA of FSHR in laying quail, which is associated with higher egg production. Another study showed that breeding geese fed on diet supplemented with 80 mg/kg vitamin E gives the highest egg number which is associated with the increase in mRNA expression of FSHR and LHR genes (Yin et al 2019). The current study agrees with Elizabith et al (2000) who stated that FSH exert its role by its specific receptor (FSHR) in the development and maturation of the follicles and cooperates with LH in the ovulation process.…”
Section: Discussionsupporting
confidence: 91%